(untitled) - Sandler, Todd (Cambridge, U.K., 2001)
The primary purpose of this book is to present some of the key economic concepts that have guided economic thinking in the last century and to identify which of these concepts will continue to direct economic thought in the coming decades. This book is written in an accessible manner and is intended for a wide audience with little or no formal training in economics.
Keywords: Economics,Social sciences; History,History; 20th century,20th century